Respuesta :

General equation of parabola

  • y=a(x-h)²+k

for vertex(h,k)

Now

[tex]\\ \rm\Rrightarrow y=a(x+2)^2+6[/tex]

  • Put (1,-3) and find a

[tex]\\ \rm\Rrightarrow -3=a(1+2)^2+6[/tex]

[tex]\\ \rm\Rrightarrow -9=a(3)^2[/tex]

[tex]\\ \rm\Rrightarrow -9=9a[/tex]

[tex]\\ \rm\Rrightarrow a=-1[/tex]

So

equation of parabola

[tex]\\ \rm\Rrightarrow y=-(x+2)^2+6[/tex]

Ver imagen Аноним

Answer:

[tex]y=-(x+2)^2+6[/tex]

Step-by-step explanation:

Vertex form of a quadratic equation

[tex]y=a(x-h)^2+k[/tex]

where:

  • (h, k) is the vertex
  • a is some constant

Given:

  • vertex = (-2, 6)
  • point on parabola = (1, -3)

Substitute the given values into the vertex equation and solve for a:

[tex]\implies -3=a(1-(-2)^2+6[/tex]

[tex]\implies -3=a(3)^2+6[/tex]

[tex]\implies -3=9a+6[/tex]

[tex]\implies 9a=-9[/tex]

[tex]\implies a=-1[/tex]

Vertex form

Substitute the given vertex and the found value of a into the vertex equation:

[tex]\implies y=-(x+2)^2+6[/tex]

Standard form

Expand the brackets of the vertex form:

[tex]\implies y=-(x^2+4x+4)+6[/tex]

[tex]\implies y=-x^2-4x+2[/tex]

Ver imagen semsee45